839. Epidemiology of Extended-Spectrum Beta-lactamase (ESBL) Producing Enterobacteriaceae in the South East Tennessee, October-December 2017. (31st December 2020) - Muleta, Daniel; Adre, Cullen; Warner, Benji-Byrd
Abstract: Background: The increasing spread of drug resistant gram-negative organisms is one of the major public health challenges. ESBL-producing Enterobacteriaceae has become the most common multi drug resistant pathogen in the last three decades. These organisms confer resistance to most beta-lactam antibiotics, including penicillins, third generation cephalosporins, monobactams and tazobactam. Methods: The Tennessee Health Department (TDH) collaborated with CDC to pilot population based surveillance of ESBL producing organisms in Maury, Wayne, Lewis and Marshall Counties during October to December 2017. A case was defined as isolation of Escherichia coli, Klebsiella pneumoniae, or Klebsiella oxytoca resistant to at least one extended-spectrum cephalosporin (ceftazidime, cefotaxime or ceftriaxone) and non-resistant to all carbapenem antibiotics from urine or normally sterile body sites from a resident of the surveillance catchment area. A line list of ESBL-producing organisms was received from the labs that serve the catchment population. Case report forms were completed for the first ESBL culture collected from a single patient in a 30 day-period. Results: A total of 154 cases were identified during the study period . E.coli constitutes 92.2% of the ESBL producing organisms followed by Klebsiella pneumonia (5.2%) and K. oxytoca (2.6%). The estimated annual incidence rate was 400.7 per 100, 000 population which is more than twice of the average rates of other sites that conducted similar studies. The most common isolate source was urine (97%), and 81.2% of all cases were female. Patient ages ranged from 3-99 years, with average of 67 years. Thirty-two isolates underwent additional sequence typing and 76.7% (23) of the isolates were ST 131. 21 (91.3%) of ST-131 isolates were resistant to ciprofloxacin. Conclusion: The study revealed that the incidence of ESBL producing organisms is very high in the Tennessee study area compared to other sites. The most common ESBL-producing pathogen was found to be ST 131 and most of these were resistant to ciprofloxacin suggesting that resistance to fluoroquinolone may be co-transmitted in ESBL producing pathogens through plasmids. Continued surveillance of molecular epidemiology is important to guide the prevention of the spread of drug resistant pathogens. Disclosures: All Authors : No reported disclosures